Independence of The Auditor Inspectorate of Regional Supervision of The North Sulawesi Police in Conducting The Audit at The Polres Tomohon - Rumate, Djonny; Langkkai, Jeane Elisabeth; Kairupan, Sisca Beatrix (Technium Social Sciences Journal, 2022)
This study aims to analyze the independence of the auditors of the Regional Supervision Inspectorate of the North Sulawesi Regional Police in conducting audits at the Tomohon Police Station. This study uses a qualitative descriptive approach, which seeks to analyze the independence of the internal auditors of the North Sulawesi Regional Police Inspectorate in conducting internal audits at the Tomohon Police Station. This research is focused on the freedom of internal audits related to external disturbances such as a). interference from external parties in the form of interference that limits the examination scope, b). selection and application of inspection procedures, c). time restrictions, assignments, d). appointment and promotion auditor examiner, e). constraints on the resources used, e). the authority to influence the examiner's consideration of the contents of a report on the examination results, f). the threat of replacement of the examiner for disagreement with the contents of the audit report concluded the examiner [39]. Research informants are auditors on duty between the odd-even semesters of 2020/2021 at the Tomohon Police, namely: a). Middle Auditor, b). Field Inspector (Irbid), c). Head of the inspectorate, d). Treasurer, e). Head of the Tomohon Police Supervision Section. Secondary data was obtained through audit report documents. The data analysis technique uses the Miles and Huberman interactive model. The conclusions of this study are a). Not yet independent because of the intervention of external parties that limit the audit scope, b). Not yet separate in selecting and implementing audit procedures, c). Not yet different because there is a limitation on assignment time, d). Not yet different due to the appointment and promotion of auditors, e). Not yet in a separate cause of restrictions on the resources used, f). Not yet in a different cause of the authority to influence the examiner's judgment on the contents of a report on the examination results. For this reason, it is recommended that: a). the rank, position overcome interference from external parties that limit the scope of the audit, and work experience of the auditor being higher than that of the auditee, b). selection and application of inspection procedures are adjusted to the field conditions of the Tomohon Police, c). Sufficient time is given by considering disturbances caused by field conditions, d). the appointment and promotion of the auditor examiner are adjusted to the auditee's rank, position, and work experience, e). Equipped with the availability of adequate resources according to the needs of the audit, f). the authority to influence the examiner's consideration of the contents of a report on the results of the examination is limited by the internal policy of Irwasda Polda.